Smart 3-wheel bike "empower disabled entrepreneurs with technology" / Nurnaddia Nordin, Nurhaiza Nordin and Nur Ilyana Amiira Nordin - Nordin, Nurnaddia; Nordin, Nurhaiza; Nordin, Nur Ilyana Amiira (2021)
Technology is a crucial factor for starting a business today and it is an important factor for disabled entrepreneurs. Entrepreneurship has become one of the preferred fields of employment for disable people due to lack of other employment opportunities. However, the existing technology for disabled people is still insufficient to ensure that disabled people remain competitive in the entrepreneurship field. The Smart 3-Wheel Bike was developed with the aim of providing better facilities to entrepreneurs with disabilities. The process of developing this product is based on three phases, analysis phase, design and development phase and finally implementation and evaluation phase.